An Investigation into the Grade Dynamics of Drainage Implements - Magalhäes, Paulo Sergio Graziano (Cranfield University, 1985)
The use of the trenchless plough drainage implement has increased in the past few years due to its efficiency and cost advantages over other methods. However, the performance of these machines when working in fields with irregular soil conditions is not yet satisfactory. It is important therefore to study the soil parameters and conditions which could affect the implement behaviour under these circumstances. Therefore, a detailed investigation of the soil reaction forces acting upon a scale model of the trenchless plough was conducted under controlled conditions in a soil laboratory. The model was tested first under restricted conditions of movement, in order to observe and determine all the possible soil reaction forces. The tine, due to its geometric characteristics, was classified as a very narrow tine, and an existing model to predict the soil reaction force acting on the front face of these tines was extended to predict the forces on the sides. Since the length of the failure plane ahead of the tine is often required in the investigation of the soil reaction forces, a mathematical solution based on the Coulomb principle of Passive Earth Pressure was presented to estimate the soil failure pattern. There was good agreement between the values of the angle of the shear plane predicted by this method and the experimental data obtained from the glass sided tank tests. Dynamic tests were conducted with the implement assembled with a long floating beam arrangement assisted by a small link (free-link), used between the hitch-point and the pivoted end of the beam. These tests revealed that, when working over irregular soil conditions a better grade control can be obtained if the hitch-point is kept at constant level in reference to a desired line. In the case where field irregularities persist for long (step inputs), corrections in the hitch-point height might be necessary. These tests show that the implement depth changes in different proportion in relation to the hitch-point height. Where no control is imposed on the hitch-point, the path of the implement is attenuated in relation to the hitch-point position, where better results are obtained for high frequency of the hitch-point. A mathematical solution based on these findings and on the dynamic balance of the forces acting on the system was presented. Since it is an interactive method and requires long and repetitive calculations, a computer programme was developed and used to predict the response of the implement under these uneven conditions. Good agreement between data and estimated values suggested that the method is acceptable.